2010
DOI: 10.1590/s0004-27302010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein quality on appetite and energy metabolism in normal weight subjects

Abstract: Objective: The purpose of this study was to compare the effects of consumption of different protein sources on food intake and energy expenditure in normal weight subjects. Subjects and methods: Breakfast preparations (casein, soy protein, whey protein or control) were ingested during seven consecutive days. Appetite, food intake, and energy expenditure were assessed. Results: Casein consumption led to a lower energy intake than whey protein. There was lower energy intake on day 7 than on day 1 of the casein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…16,17 In the present study, whey, casein and milk had similar effects on acute appetite sensation, but ad libitum EI at the subsequent lunch was significantly decreased by milk compared with the casein and the whey beverages. There was no significant difference in EI after the whey and the casein beverages.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…16,17 In the present study, whey, casein and milk had similar effects on acute appetite sensation, but ad libitum EI at the subsequent lunch was significantly decreased by milk compared with the casein and the whey beverages. There was no significant difference in EI after the whey and the casein beverages.…”
Section: Discussionsupporting
confidence: 47%
“…Cumulative lipid oxidation was greater after the whey, casein and soy meals than after the high carbohydrate meal, and tended to be greater after the whey meal than after the soy meal (P ¼ 0.097). By contrast, Alfenas et al 17 observed a significantly higher DIT after a breakfast meal containing soy compared with a breakfast meal containing carbohydrate, but no significant difference in DIT after breakfast meals with soy, whey and casein. The respiratory quotient was significantly low after whey compared with soy, whereas casein was not significantly different from either whey or soy.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Glycemic index was also included within these diets but is not included in this discussion. In the adults who completed the study, the higher-protein diet led to less weight regain (MD: 20.93 kg; 95% CI: 20.31, 21.55 kg; P = 0.003) than the lower-protein diet did (66). The children who followed the higher-protein regimen had reductions in waist circumference (22.7 cm; 95% CI: 0.9, 5.1 cm; P , 0.007) and LDL cholesterol (20.25 mmol/L; 95% CI: 0.09, 0.41 mmol/L; P , 0.007) compared with those following the lower-protein version (78).…”
Section: Clinical Outcomes With Long-term Higher-protein Diets Of ‡1 Ymentioning
confidence: 93%
“…Although the impact of protein quality on appetite control and food intake is poorly characterized, there are data, albeit inconsistent, that show protein-source effects. In some (62,63), but not all (64)(65)(66), studies the consumption of whey protein elicited a greater reduction in postprandial hunger and a greater increase in postprandial satiety than consumption of casein and/or soy. The contribution of protein quality on these outcomes is further supported by the Veldhorst et al (50,51) studies that compared higher-with lower-protein meals but included different types of protein.…”
Section: Appetite and Subsequent Food Intake After Higher-protein Mealsmentioning
confidence: 93%